1987
DOI: 10.1073/pnas.84.23.8740
|View full text |Cite
|
Sign up to set email alerts
|

Linear mechanisms of directional selectivity in simple cells of cat striate cortex.

Abstract: The role of linear spatial summation in the directional selectivity of simple cells in cat striate cortex was investigated. The experimental paradigm consisted of comparing the response to drifting grating stimuli with linear predictions based on the response to stationary contrast-reversing gratings. The spatial phase dependence of the response to contrast-reversing gratings was consistent with a high degree of linearity of spatial summation within the receptive fields. Furthermore, the preferred direction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
142
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 19 publications
13
142
2
Order By: Relevance
“…Could these stimulus-related changes at the perceptual level originate from changes in the properties of single cortical DS cells, or do they simply reflect a population of diverse, but individually fixed, temporal RF profiles? Fixed RFs are consistent with demonstrations that linear spatiotemporal filters account well for response properties including direction selectivity in V1 simple cells (Movshon et al, 1978;Reid et al, 1987;Palmer, 1989, 1994;DeAngelis et al, 1993), but there have been some reports of stimulus-related changes in temporal integration in simple and complex cells in cats and monkeys (Dean et al, 1982;Reid et al, 1992).…”
Section: Introductionsupporting
confidence: 52%
“…Could these stimulus-related changes at the perceptual level originate from changes in the properties of single cortical DS cells, or do they simply reflect a population of diverse, but individually fixed, temporal RF profiles? Fixed RFs are consistent with demonstrations that linear spatiotemporal filters account well for response properties including direction selectivity in V1 simple cells (Movshon et al, 1978;Reid et al, 1987;Palmer, 1989, 1994;DeAngelis et al, 1993), but there have been some reports of stimulus-related changes in temporal integration in simple and complex cells in cats and monkeys (Dean et al, 1982;Reid et al, 1992).…”
Section: Introductionsupporting
confidence: 52%
“…Inseparable simple cell receptive fields have been described in detail (Albrecht and Geisler 1991;Dean and Tolhurst 1986;DeAngelis et al 1993;Jagadeesh et al 1997;McLean and Palmer 1989;McLean et al 1994;Movshon et al 1978;Murthy et al 1998;Reid et al 1987;Saul and Humphrey 1992b). Several clear results have emerged.…”
Section: Asymmetry In Inputs To Ds Cellsmentioning
confidence: 89%
“…Simple cell spiking responses deviate significantly from linear expectations, but the underlying basis for the differences between predicted and actual values is unclear. Spiking responses based on noise stimulation systematically underestimate spiking selectivity for orientation tuning (Gardner et al 1999), spatial and temporal frequency (DeAngelis et al 1993b), direction (Albrecht and Geisler 1991;DeAngelis et al 1993b;Reid et al 1987Reid et al , 1991, and binocular disparity . As in previous reports, we found that our expectation of response (GP SP ), derived from the spiking responses to the noise stimulus, is related to recorded spike rate in a nonlinear fashion (Fig.…”
Section: Resultsmentioning
confidence: 99%